Pathophysiological mechanisms of ARDS: a narrative review from molecular to organ-level perspectives - Kaihuan Zhou; Qianqian Qin; Junyu Lu (Respiratory Research)
Abstract Background Acute respiratory distress syndrome (ARDS) remains a life-threatening pulmonary condition with persistently high mortality rates despite significant advancements in supportive care. Its complex pathophysiology involves an intricate interplay of molecular and cellular processes, including cytokine storms, oxidative stress, programmed cell death, and disruption of the alveolar-capillary barrier. These mechanisms drive localized lung injury and contribute to systemic inflammatory response syndrome and multiple organ dysfunction syndrome. Unlike prior reviews that primarily focus on isolated mechanisms, this narrative review synthesizes the key pathophysiological processes of ARDS across molecular, cellular, tissue, and organ levels. Main body By integrating classical theories with recent research advancements, we provide a comprehensive analysis of how inflammatory mediators, metabolic reprogramming, oxidative stress, and immune dysregulation synergistically drive ARDS onset and progression. Furthermore, we critically evaluate current evidence-based therapeutic strategies, such as lung-protective ventilation and prone positioning, while exploring innovative therapies, including stem cell therapy, gene therapy, and immunotherapy. We emphasize the significance of ARDS subtypes and their inherent heterogeneity in guiding the development of personalized treatment strategies. Conclusions This narrative review provides fresh perspectives for future research, ultimately enhancing patient outcomes and optimizing management approaches in ARDS.